1977
DOI: 10.1111/j.1432-1033.1977.tb11766.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Factor from Enteric Bacteria of Rats Amplifying Induction of Liver Enzyme by Glucocorticoid. 1. Purification, Properties and Biological Action

Abstract: 1. A factor, which amplifies the inductions of several liver enzymes by glucocorticoid, was partially purified from Proteus mirabilis from rat intestine. The factor (amplifier) was completely inactivated by ct-glucosidase, but not by other glycoside hydrolases, proteases, nucleases or phosphatases tested; it was also hydrolysed by HCI with liberation of reducing sugars. Thus the oligosaccharide in this factor seems to be essential for the amplification.2. In adrenalectomized rats the amplifier increased the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As there was no difference in the leucine pool in livers among germ-free, con ventionalized and conventional mice (Table 1), these results indicate that the utilization of amino acids (the incorporation of amino acids into liver-soluble protein) was increased in the host liver by some action of intestinal flora. This increase in the synthesis of liver protein probably was not due to the cortisone amplifying factor produced by intestinal flora (11,12), which is believed to induce only certain specific liver proteins but not total liver protein. Further studies are needed to define the mechanism by which intestinal flora increase protein synthesis in the liver of host animals.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As there was no difference in the leucine pool in livers among germ-free, con ventionalized and conventional mice (Table 1), these results indicate that the utilization of amino acids (the incorporation of amino acids into liver-soluble protein) was increased in the host liver by some action of intestinal flora. This increase in the synthesis of liver protein probably was not due to the cortisone amplifying factor produced by intestinal flora (11,12), which is believed to induce only certain specific liver proteins but not total liver protein. Further studies are needed to define the mechanism by which intestinal flora increase protein synthesis in the liver of host animals.…”
Section: Resultsmentioning
confidence: 92%
“…For some decades, many studies have been made on the influence of non-pathogenic flora on morphological and biological changes of intestinal mucosa (4,5), intestinal peristalysis (6), the accumulation of nitrogen (7) and the amount of amino acids in the intestines of host animals (8-10). Recently, it was found that some compounds produced by intestinal flora amplify the cortisone effects including enzyme induction (11,12). This finding suggested the participation of intestinal flora in the regulation of metabolism in the host animal.…”
Section: Resultsmentioning
confidence: 98%
“…It has also been reported that the presence of intestinal microflora may contribute something to the improvement of vitamin B6-deficiency in animals (6)(7)(8). Recently, KATUNUMA et al showed that intestinal microflora synthesized a new factor which enhanced several actions of glucocorticoid (9), and glucocorticoid was an inducer of aminotransferases of alanine, aspartate and tyrosine (10,11). These reports suggest that the activities of vitamin B6-dependent enzymes in conventional rats may differ from those in germ-free rats which retain no intestinal microflora.…”
Section: Discussionmentioning
confidence: 99%
“…There were considerable decreases in aspartate aminotransferase activities from erythrocytes and in alanine aminotransferase activities from liver between conventional control and germ-free control rats. Since it has been reported that a factor enhancing glucocorticoid actions was synthesized by intestinal microflora in animals (9), and glucocorticoid induced alanine and aspartate aminotransferases in liver (10,11), the considerably high activities of their enzymes in conventional control rats might indicate the effect of the factor synthesized by intestinal microflora in conventional rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the findings that many compounds, such as interferon, muramyl dipeptide, thymosin ab and various lymphokines, modulate immunological responses have led to the concept of "biological responses modulators" (Ivarie & O '-Farrell, 1978). In the case of hormonal responses, we have long proposed the existence of modulators that specifically enhance the actions of glucocorticoids in target organs or cells (Katunuma et al, 1971(Katunuma et al, , 1977Kido et al, 1977), and these modulators have recently been summarized and termed "glucocorticoid action biomodulators" (Kido et al, 1986).…”
mentioning
confidence: 99%